The Direct Method in Language Teaching: A Literature Review of Its Effectiveness - Andi Muhammad Dakhalan; Jem Cloyd M. Tanucan (Lingeduca: Journal of Language and Education Studies, 2024)
The Direct Method in language teaching, which emphasizes teaching language through immersion and avoiding the use of the learner’s native language, has been widely used in educational settings for over a century. Its focus on oral communication, everyday vocabulary, and inductive grammar teaching has made it a popular approach. However, debates about its effectiveness compared to more modern teaching methods have persisted, particularly in terms of long-term language acquisition and proficiency. This literature review aims to evaluate the effectiveness of the Direct Method by analyzing studies conducted across various educational contexts. The review examines how this method impacts learners’ speaking, listening, and overall communicative competence. By synthesizing both qualitative and quantitative research, the study provides a comprehensive view of the strengths and limitations of the Direct Method. The findings indicate that while the Direct Method improves oral proficiency and listening skills in the short term, it may not be as effective for developing reading and writing skills. Studies show that the method fosters greater student engagement and motivation but may not adequately address the complexities of advanced grammar and academic language. Furthermore, the method’s effectiveness depends heavily on the teacher’s skill in creating immersive language environments. In conclusion, the Direct Method offers valuable benefits for beginner and intermediate learners, especially in communicative aspects of language. However, it requires supplementation with other approaches to develop comprehensive language proficiency. Future research should explore ways to integrate the Direct Method with more advanced instructional techniques for a balanced approach to language teaching.